Rab35-dependent extracellular nanovesicles are required for induction of tumour supporting stroma. Issue 18 (25th April 2018) - Yeung, V.; Webber, J. P.; Dunlop, E. A.; Morgan, H.; Hutton, J.; Gurney, M.; Jones, E.; Falcon-Perez, J.; Tabi, Z.; Errington, R.; Clayton, A.
Abstract : A subpopulation of secreted nano-vesicles is critical for microenvironment changes, driving tumour growth. Abstract : Communication between diseased cells and the microenvironment is a complex yet crucial element in progression of varied pathological processes. Recent studies in cancer highlight an important role for small extracellular nanovesicles secreted by cancer cells as modulators of cancer-associated stroma, leading to enhanced angiogenesis and metastatic priming. The intrinsic factors regulating extracellular nanovesicle biogenesis and secretion are therefore relevant in studies of nano-communication in the cancer milieu. We generated prostate cancer cells bearing stable knockdown of several candidate vesicle regulating factors and examined the impact on cell health, vesicle secretion and on communication with fibroblastic stromal cells. We highlight that RAB11B and RAB35 regulate phenotypically distinct nanovesicle populations, each accounting for only around 20% of the total. Depleting RAB35, but not RAB11B leaves a remaining population of vesicles whose phenotype is insufficient for driving fibroblast to myofibroblast differentiation, leading to attenuated motile behaviours in 3D in vitro models. Co-implantation of tumour cells with stromal fibroblasts in xenografts similarly showed that RAB11B knockdown had little effect on growth rates in vivo . In contrast, significant attenuation in growth, and attenuation of myofibroblasts at the tumour site was evident when using RAB35-knockdown cells. The study concludes that a RAB35 regulated nanovesicle sub-population is particularly important for communication between cancer and stromal cells, and is required for generating a tumour-supportive microenvironment.